Фотоелектричні властивості кристалу AgGaGeS4 - Мирончук, Галина; Парасюк, Олег; Кримусь, Андрій; Myronchuk, Galyna; Parasyuk, Oleh; Krymus, Andrii (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У роботі досліджено кінетику релаксації фотопровідностів в монокристалі AgGaGeS4 Установлено, що час релаксації фотопровідності в кристалах AgGaGeS4 залежить від інтенсивності освітлення та температури. Оцінено глибину залягання пастки. ; Kinetics of photoconductivity relaxation in AgGaGeS4 crystal has been investigated in this work. It has been established that photoconductivity relaxation time in AgGaGeS4 crystals depends on light intensity and the temperature. The depth of trap has been estimated from the experimental data.
Photoelectric Properties of AgGaGeS4 Crystal
Keywords: релаксація фотопровідності; пастка; час релаксації; photoconductivity relaxation; trap; relaxation time